(untitled) - Strickberger, Monroe W. (London, 1996)
Various chapters are devoted to topics that include the historical development of evolutionary thought, cosmological and geological events, evolution of genetic systems and molecular pathways, and accounts of organisms from plant to human. In studying the history of life, students will begin to recognize the interrelatedness of many scientific fields
Keywords: Evolution ( biology )